Pembangunan Dan Perkembangan Hukum Investasi Hubungan Industrial Di Indonesia Dalam Perspektif Hukum Integratif - Zaenudin, KM Ibnu Shina; Risnandar, Aep (CV. Era Digital Nusantara, 2025)
Investment is one of the main pillars of a country's economic development, but it often faces the complexities of industrial relations issues that can significantly affect the investment climate. Investmentlaw in Indonesia has undergone various changes in line with global and domestic economic dynamics,including efforts to attract investment thru various incentives. On the other hand, industrial relations lawseeks to create fairness and balance between the rights and obligations of employers and workers. ProfessorRomli Atmasasmita's integrative legal approach, which emphasizes the harmonization of various branchesof law to achieve development goals, is relevant for analyzing how these two legal fields can synergize or,conversely, create disharmony in practice. This research aims to identify the challenges and opportunitiesin integrating investment law and industrial relations law to create a conducive investment climate whileensuring justice for workers. The conclusion of this research is that, so far, Indonesian investment law andindustrial relations have operated separately, creating disharmony. An integrative approach is needed forharmonization and balancing social economic goals, therefore, the Job Creation Law needs to be revised tofocus more on integrating worker protection and investment with the aim of synergizing economic growth and welfare.